The ends of critique methods, institutions, politics - Thiele, Kathrin, 1972-; Kaiser, Birgit Mara; O'Leary, Timothy, 1966- (New critical humanities., 2021)
"The Ends of Critique re-examines the stakes of critique in the 21st century. In view of increasingly complex socio-political realities and shifts in a fully globalized world, the roles and manners of critique also change. The volume offers an unprecedented re-examination of critique under those conditions of global entanglement and asymmetrical relations from a diversity of scholarly perspectives within the humanities. All contributions move the notion of critique into more diverse traditions than the Eurocentric, Kantian tradition and emphasize the need to attend to a plurality of critical perspectives. The volume's reflections move critique toward a situated, perspectival, and entangled critical stance, with interventions from decolonial and systemic, deconstructive and (post)human(ist) perspectives. In that way, the volume develops a decidedly different approach to critique than recent considerations of critique as post-critique (Felski) or those endebted to Frankfurt School thought and liberal theories of democracy. It is the first full-length research publication of the interdisciplinary research network Terra Critica"--